Multicentric Castleman disease with TAFRO syndrome and Sjögren's - Zi Ying Li; Shirley Kim; SiYi Huang; Raza Mian (Clinical Case Reports, 2019)
Abstract We describe a patient with Castleman's disease with TAFRO syndrome and concurrent Sjögren's syndrome and investigate whether the autoimmune process may have accelerated the onset of her Castleman's disease. Patient was treated with R‐CVP therapy with remission of symptoms although there is no current standard treatment.